2009
DOI: 10.1007/s00239-009-9267-9
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Adaptation for Eight Microvirid Bacteriophages

Abstract: Theories of adaptive molecular evolution have recently experienced significant expansion, and their predictions and assumptions have begun to be subjected to rigorous empirical testing. However, these theories focus largely on predicting the first event in adaptive evolution, the fixation of a single beneficial mutation. To address longterm adaptation it is necessary to include new assumptions, but empirical data are needed for guidance. To empirically characterize the general properties of adaptive walks, eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(126 citation statements)
references
References 70 publications
8
110
4
1
Order By: Relevance
“…Our result (25) shows that the walk should last longer in systems with smaller κ. This may be checked by measuring the mean walk length in populations with κ = −1 [16], κ → 0 [15] and κ > 0 [11]. To find the dependence of walk length properties on L, varying the sequence length may not be experimentally viable but it should be possi-ble to set up experiments along the lines of [9] and vary the initial fitness rank.…”
Section: Equation (3) and Changing The Variable To Z = (1+κf )/Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result (25) shows that the walk should last longer in systems with smaller κ. This may be checked by measuring the mean walk length in populations with κ = −1 [16], κ → 0 [15] and κ > 0 [11]. To find the dependence of walk length properties on L, varying the sequence length may not be experimentally viable but it should be possi-ble to set up experiments along the lines of [9] and vary the initial fitness rank.…”
Section: Equation (3) and Changing The Variable To Z = (1+κf )/Lmentioning
confidence: 99%
“…The fitness distribution p(f ) lies in the domain of the extreme value distribution given by Weibull distribution for κ < 0, Gumbel distribution if κ → 0 and Fréchet distribution for κ > 0. Although much of the experimental data on distribution of beneficial mutations is consistent with κ → 0 [9,15], recent works also support κ < 0 [16] and κ > 0 [11]. The adaptive walk in the limits κ → ±∞ is well studied theoretically.…”
mentioning
confidence: 93%
“…In an evolutionary study of eight Microviridae phages, Rokyta and colleagues observed that the majority of mutations detected at the end of an evolutionary walk were missense changes that occurred in genes coding for structural proteins (gpF, gpG, gpH, and gpJ) (23). Five missense mutations were found in the G gene.…”
Section: Figmentioning
confidence: 99%
“…Many studies have been conducted to better understand how ssDNA viruses evolve, and at least two different approaches have been used to investigate Microviridae evolution. The first approach involves replication of viruses in a chemostat with and without different selective pressures for many generations (15)(16)(17)(18)(19)(20)(21)(22)(23). The second approach is based on isolating and sequencing novel members of the virus family (24) and surveying environmental sequences (25).…”
mentioning
confidence: 99%
“…Minél nagyobb hatása van egy gén elvesztésének, annál könnyebb ezt a hatást enyhíteni. Korábbi kis skálájú vizsgálatok is találtak ilyen összefüggést [Moore et al, 2000, Estes and Lynch, 2003, Poon and Chao, 2005, Rokyta et al, 2009, és nemrég napvilágot látott több publikáció is, melyek nagyobb skálán és más organizmusok esetén is megerősítették eredményünket [Couce andTenaillon, 2015, Blank et al, 2014]. Több okból is kialakulhat a megfigyelt mintázat.…”
Section: Diszkusszióunclassified